Noise and Hearing Conservation - M, Pancholy (Journal of All India Institute of Speech and Hearing, 1970)
Noise is now recognised as a nuisance and there is a growing awareness in the society about its deleterious effects on general well being, efficiency of work and health. Leaving out the extreme cases of mild noise causing irritation to psychologically or physically predisposed subjects and very intense noises which may be a health hazard, the disturbing effect of noises in general is divided under three main categories: (i) annoyance to listener, (ii) interference with speech communication and (iii) risk of impairment of hearing.